An Introduction Study Of Density And Land Use In Urban Area - Malik I B; Dewancker B J (International Conference on Engineering and Technology Development (ICETD), 2017)
The proportion of urban land must have a balance, because it can affect the progress or decline of the city. An unbalanced proportion will cause flooding, drought, pollution, and food production problems. Bandar Lampung which is the location of research on the proportion of land shows the fact that BWK (urban zone) has the main function of more than one function that can threaten each other. To facilitate analysis, the main function of the city is divided into three groups: business, conservation, and other functions. This study shows that business functions use 60.29% of urban area, 21.70% conservation, and other functions 18.02%. The conservation area is in danger of diminishing as conservation functions are mixed with residential and business functions. Bandar Lampung requires a moratorium policy on opening new land for business activities (economy and settlements), but simultaneously encouraging the increase of conservation land area. Bandar Lampung requires the refinement of urban planning documents and improving urban spatial policy